Parametric study of portable solar-powered heat exchanger using computational fluid dynamics - Tengku Ibrahim, Tengku Muhammad Fahmi (2016)
Water is important for human. Its importance is highlighted by the United Nation as decade for clean water in the world populations suffer lack of portable water in stressed area such as Africa and South East Asia. Therefore, solar powered water distillation system is important, especially for portable devices seems necessary. This study is concerned with parametric of heat exchanger for a portable telescopic solar powered water distiller. The water supply for the distiller is untreated water from rain water, tube well or flood water. The solar powered water distiller was a Master thesis project completed in 2014 but the heat exchanger requires further improvement on design and fabrication. Presently, the water distiller can produce 10L per day in good sunny weather. The shell and tube heat exchanger with parabolic trough collector (PTC) have potential to increase performance using computational fluid dynamics to produce clean water. Design geometry of heat exchanger was based on the conditions of high-pressure difference between the fluids. The setting of cooling temperature of water inlet is 31°C and water outlet is 29.8°C. However, the tube for fluid inlet is water vapour at 82°C and the temperature outlet is at 38°C. Water vapour comes into tube heat exchanger from the parabolic thermal collector (PTC). The methodology involves using computational fluid dynamics RNG k-epsilon turbulence flow model. The model was applied using CFD (computational fluid dynamics) package conjunction with conjugated heat transfer to predict the flow behavior inside the heat exchanger for both vapour and liquid water flow. Both heat conduction and heat convection are taken into account for this 3D computational method to determine fluid flow and temperature distribution. Parameters considered for design (shell diameter, number of tubes, baffles, temperature difference, velocity of fluid and heat transfer coefficient involved) can be used to develop optimum design of heat exchanger and also through selection of suitable materials. The material construction is a very important aspect in the design for heat exchanger to ensure operating conditions fabrication technique and safe drinking water is produced at a minimum cost and low maintenance. Selected materials have to view the shape design are able to withstand high temperatures and pressures for heat exchanger to perform efficiently. The analysis compares actual experimental result and defines the suitable material and the best thermal efficiency on the shell in tube heat exchanger. A multiple baffled shell-and-tube heat exchanger design performance is evaluated numerically using CFD (computational fluid dynamics) modeling approach. The field heat exchanger consists of two tubes inside a 0.535 m long and 0.140 m diameter shell. The simulated results are found to be in good agreement with the experiment data. Different materials for the heat exchanger used are stainless steel, copper and aluminum and their performances for a heat exchanger are compared. From the results, it is found that the temperature difference between the vapour outlet and water outlet is least in the case of copper and aluminum as a solid material. Thus, it can be concluded that the copper and aluminum material is giving highest heat transfer to the water. Using copper for heat exchanger can be very expensive and the produced water is not safe to be used for drinking compared to water produced with stainless steel. High heat transferred to the water will help in the sanitising process of the water. Sanitising is a process in which water is cleaned by the use of heat, to turn the water into a usable form.